Network analysis of Beowulf, the Iliad and the Táin Bó Cúailnge - Mac Carron, P; Kenna, R (Lit Verlag, 2014)
Mythological epics frequently entail plethoras of characters in timeless narratives beyond documented history. As such, they differ from legends couched in definite historical timeframes and intentionally fictional folktales. The concept of universality is important to comparative mythology and it has been claimed that narratives from a variety of cultures share similar structures. Universality also lies at the heart of network theory, a relatively new branch of theoretical physics with broad applicability. Network theory allows one to classify and compare the interconnectedness underlying a multitude of structures relevant to biology, sociology, economics, chemistry, physics, transport, computer science, and other disciplines. Here we apply this theory to study networks of characters appearing in three different mythological narratives: Beowulf, the Iliad and the Táin Bó Cúailnge. By comparing these amongst each other, and to real, fictitious and random networks, we seek to develop a new, quantitative approach to comparative mythology. In particular, we find that each of the three epics has, to varying degrees, properties akin to those of real social networks. This quantitative approach forms a basis upon which one may speculate as to the extent to which these narratives may be based upon real or imaginary societies.